TERTULLIAN, DE RESURRECTIONE CARNIS LXIII: A NOTE ON THE ORIGINS OF MONTANISM - Davies, J. G. (The journal of theological studies, 1955)
J. G. DAVIES; TERTULLIAN, DE RESURRECTIONE CARNIS LXIII: A NOTE ON THE ORIGINS OF MONTANISM, The Journal of Theological Studies, Volume VI, Issue 1, 1 April 195